Meclis gizli celse zabıtlarında Başkomutanlık meselesi - Tunç, Hasan (My University, 1999)
ABSRACT The chief of the Army ıssve in the documents of the secret sessions of National Assembly. Mustafa Kemal's journey started in Samsun in May 19, 1919, contunied in Amasya, Erzurum, Sivas and then Ankara, and finally ended in İzmir in September 9, 1922, formed the History of National Independence. The Independence was grounded in on many bloody wars, agony, and struggle beyond man power. The chief actors of this struggle, of course, were Mustafa Kemal and a few people who dedicated their lives to this struggle. Each phase of the Independence war is of great importance, and consequently each of them deserves tedailed investigation. But the destiny of the war got clear after Sakarya and the following wars. The victory in these wars gave rise to our Turkish Republic. Hence, Sakarya The Chief of Army and the Great Assault are significant. The case of losing one of these wars would have put an end to our final goal, Turkish Republic. Thus, in this thesis,the chief of the Army title assigned to Mustafa Kemal, the secret sessions of the National Assembly about the issue were examined. To evaluate the phases mentioned above, it is a must to examine the situation that created those periods. Hence, the thesis starts with the World War I, which gave rise to the foundation of the Republic of Turkey. In the first chapter, the causes of World War I, the situation of Ottoman Empire and Europe, the plans about Ottoman Empire, and the result, of the World War I were examined. Mondros Treaty which put an end to the war and caused Ottoman Empire to collapse, the situation in Istabul and Anatolia in the following period, the occupation of Anatolia, and the activities of occupant states were investigated. - 1 - The War of Independence took a start with Mustafa Kemal's disembarking in Samsun. Within the preparation phases which can be named as Getting organized through congresses, Amasya Decleration, Erzurum and Sivas Congresses played a crucial role. The policy Mustafa Kemal adopted towards the Goverment in Istanbul during this period exemplified the behaviours of a great politician. The second chapter starts, with the foundation of National Forces. The National Forces' increasingly getting strong created a big problem for the Allied Forces and the Goverment in Istanbul. Damat Ferit Pasha from whom the Allied Forces and the Sultan expected a lot to overcome this issue had to resign. Later Ali Rıza Pasha who came to power also did so. Damat Ferit who took power again was decisive to implement his bloody plans to eradicate national struggle. His ambitions and the desire of the occupant states were of priar importance. Despite all the difficulties and pressure Mustafa Kemal continued his policy and put his plans in action. The foundation of National Assembly on April 23, 1923 means the foundation of the new Turkish State. After this event more serious plans were put in action. The militia was far from to meet the demands. Hence the activities to establish a regular military force were started. The first accomplinment of these forces is the destruction of the Çerkez Ethem forces. Meanwhile, Ottoman Empire signed Sevr Treaty which meant its destruction. The third chapter starts with the military dimension of the World War I, and Inonu War I. Inonu War I and II and the events following these are mentioned. These successful was made new Turkish state to be recognized in the political arena. To put an end to this rising trend of the new state and its army, the Greek forces supported by Allied Forces stopped Turkish Forces in Kütahya-Eskişehir Wars. This event caused dissapointment within the country, and new alternative actions and plans were sought. In the assembly, the visit of a group of parliement members to the war region and front lines was decided. After this visit, the group suggested that serious precautions should be taken. Then Mustafa Kemal was assigned as the chief of the army. This idea was not Mustafa Kemal's own idea,but in the case of being assigned as the chief of army, he would not say no and refuse this duty. He accepted this duty on one condition; he wanted to have massive authority and power. He had two options; either he would become successful and a new state would be founded or would lose and be hung and Turkish nation would - 2 - be imprisoned.The ones who wanted Mustafa Kemal to have the total authurity were divided into two, on one hand there were ones who had complete confidence in him, and on the other hand ones who hoped that Mustafa Kemal would fail and dissapear. Finally, on August 5, 1921, Mustafa Kemal was assigned as the Chief of Army with extraordinary power and authority. The Sakarya War was a great succes but the 3 months period for which Mustafa Kemal was assigred as the Chief of Army ended. On November 5, this period was extended. The preparation period of the army took a long time and the opposite goups got increasingly strong. The talks on February 5, 1922 caused a lot of argument but again that period was extended for another 3 months. However, after the talks about extending that period for another 3 months on May 5, the period wasn't extended. It was a success of the oposing groups. But the army had no chief. The Assembly gathered on Mustafa Kemal's demad on May 6, extended that period for another 3 months. In the session held on July 20, 1922 Mustafa Kemal gave a speech in National Assembly and mentioned that the extraordinary situation was over and there was no need to use the power and authority of the National Assembly. After this speech the Assembly extended his duty for good. Under the command of Mustafa Kemal Chief of the Army and Great Assault resulted in great succes. A leader is a person who makes the society follow him, who has special abilities and who is consulted during the period of crisis. Society suffers a lot if it has no leader during crisis. Luckily, Turkish society had a leader during that vital period, and that leader won the war. In this study, by considering the secret sessions of the I National Assembly, I investigate the assignment of the Chief of the Army tittle to Mustafa Kemal and how it changed the direction of the war, the situation in the National Assembly, and the attitudes of the parliment members during the period of founding a new state. I would like to express my gratitude to my adrisor Assoc.Prof.Hülya BAYKAL, who has always been a great source of support and help during my study. - 3 -
Keywords: ATATÜRK, MUSTAFA KEMAL, 1881- 1938- KURTULUŞ SAVAŞI; TÜRKİYE- KURTULUŞ SAVAŞI